2007
DOI: 10.1007/s00428-007-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary neuroendocrine tumors of the gastroenteropancreatic system

Abstract: Approximately 5-10% of neuroendocrine tumors (NETs) of the gastroenteropancreatic system (GEP) have a hereditary background. The known inherited syndromes include multiple endocrine neoplasia type 1, neurofibromatosis type 1, von Hippel-Lindau disease, and the tuberous sclerosis complex. This review discusses for each of these syndromes the: (1) involved genes and specific types of mutations, (2) disease prevalence and penetrance, (3) affected neuroendocrine tissues and related clinical syndromes, (4) special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 74 publications
2
77
0
6
Order By: Relevance
“…They are rare in children (Crain & Thorn 1949). Most PanNETs are sporadic, but some may occur in inherited disorders such as MEN1, VHL and NF1 (Anlauf et al 2007a). PanNENs that are poorly differentiated (PanNECs) are rare , Hruban et al 2007).…”
Section: S8mentioning
confidence: 99%
See 1 more Smart Citation
“…They are rare in children (Crain & Thorn 1949). Most PanNETs are sporadic, but some may occur in inherited disorders such as MEN1, VHL and NF1 (Anlauf et al 2007a). PanNENs that are poorly differentiated (PanNECs) are rare , Hruban et al 2007).…”
Section: S8mentioning
confidence: 99%
“…Analysing the development of NENs of the pancreas and duodenum in multiple endocrine neoplasia type 1 (MEN1) it was found that a hyperplastic preprogrammed (i.e. hormonally differentiated) neuroendocrine cell that carries the germ line mutation of the MEN1 gene gives rise to welldifferentiated low-grade malignant neoplasms by allelic loss of the 11q13 region of the chromosome 11 (Anlauf et al 2007a,b, Perren et al 2007). In contrast, in poorly differentiated NENs, which are on the other end of the differentiation spectrum of NENs, the cell of origin is most likely close to the intestinal stem cell.…”
Section: Pathologymentioning
confidence: 99%
“…Соматостатино-мы составляют менее 1 % от всех опухолей ЖКТ [10]. Зачастую, соматостатинома сопутствует на-следственным заболеваниям: НФ 1, множествен-ной эндокринной неоплазии 1-го типа, синдрому Гиппель -Линдау и проявляется наличием объем-ного образования в поджелудочной железе (70 %) и только в 3 % случаев вовлекает ампулу Фатерова соска [11].…”
Section: Discussionunclassified
“…Only 0.2 to 0.3% of all gastrointestin REVIEWS n n 250 n 2009 n Volume 3, Number 2 nal carcinoids are localised to this region, but a quarter of these is associated with von Recklinghausen's disease [26,33,34]. Concomitant occurrence of NF1-GIST -neuroendocrine tumour has been reported in 11 cases, almost exclusively in the periampullary region [11,16,18,24,[35][36][37][38][39]. Characteristically these tumours show functional inactivity, and they have a relatively good prognosis [35].…”
Section: Associated Tumoursmentioning
confidence: 99%
“…Concomitant occurrence of NF1-GIST -neuroendocrine tumour has been reported in 11 cases, almost exclusively in the periampullary region [11,16,18,24,[35][36][37][38][39]. Characteristically these tumours show functional inactivity, and they have a relatively good prognosis [35]. At the same localisation carcinoma was observed in one case [40].…”
Section: Associated Tumoursmentioning
confidence: 99%